Williams syndrome - Gordon, Neil (Journal of Pediatric Neurology, 2006)
Williams syndrome is a rare genetically determined syndrome in which studies have shown a number of unusual physical and mental abnormalities. These may well lead to an increased understanding of the causes of the syndrome in the future. The symptoms and signs are described, especially the facial appearance, the incidence of hypercalcemia, and the cardiovascular complications. A number of studies have been done on the mental impairment of children with Williams syndrome, and their excessive friendliness is often emphasized. However, in spite of their language fluency they may well have pragmatic disorders, which warrant treatment. The learning of visual-spatial material can often be a problem, and one that persists into adult life. The cerebral pathology shows a number of correlations with clinical findings, such as the learning difficulties, in particular visual processing; hyperacusis; and unexpected musical skills. The clinical findings will suggest the diagnosis, but this may well depend on having seen similarly affected children before; and will be confirmed by genetic studies. The prognosis can be favorable. Treatment can help the symptoms of hypercalcemia and hypothyroidism, and surgery for aortic supravalvular stenosis is sometimes possible.
Keywords: Williams syndrome; symptoms; signs; pathology; diagnosis; treatment